Disability: A new vision. Contributions of the winnicottian psychoanalysis - Amiralian, Maria Lucia de Toledo Moraes (Clinical Styles. The Journal on the vicissitudes of childhood, 2003)
Disability is a problematic issue and has induced many psychologists to be involved in this area and has promoted important debates on this subject. Understanding the development of these persons from the point of view of Winnicottian concepts has brought out important modifications in their attendance. Works already made based on those concepts show fundamental aspects to be carefully considered: a) the understanding of the constitution of human being as a mutual interation between the biological organism and the environment that supports him, b) the understanding of the disability as a basic condition, not a corrigible accessory, c) the understanding of the risk (dangers, or alterations) to which these persons are exposed.